Petrocultures : oil, politics, culture - Wilson, Sheena; Carlson, Adam; Szeman, Imre (McGill-Queen's University Press, 2017)
"The character of contemporary life depends fundamentally on oil--a cheap, accessible, and rich source of energy that has fuelled the shape of our cities, manufacturing economies, global trade, auto-mobility, and more. And yet it is only over the past decade that full recognition of oil's social and cultural significance has become a prominent feature of everyday debate and discussion. Petrocultures: Oil, Politics, Culture offers a multifaceted analysis of the cultural, social, and political claims and assumptions that guide how we think and talk about oil. This interdisciplinary collection of essays offers a map of the complex and often contradictory ways in which oil has come to be positioned in public imaginaries around the world. While oil is a physical substance, it only holds the significance it does for publics around the world as a result of the social and historical narratives and processes that enable its extraction and which shape the cultural forms, experiences, and expectations within which it circulates. The ground breaking energy humanities essays collected in Petrocultures investigate the narratives and discourses surrounding oil in contemporary culture, so that we might more fully understand its true social role and significance--and what it might mean to shift to cultures no longer shaped so deeply by fossil fuels."--